Bergamo and Covid-19: How the Dark Can Turn to Light - Perico, Norberto; Fagiuoli, Stefano; Di Marco, Fabiano; Laghi, Andrea; Cosentini, Roberto; Rizzi, Marco; Gianatti, Andrea; Rambaldi, Alessandro; Ruggenenti, Piero; La Vecchia, Carlo; Bertolini, Guido; Paglia, Stefano; et al. (Frontiers in Medicine, 2021)
The novel coronavirus, SARS-CoV-2, continues to spread rapidly. Here we discuss the dramatic situation created by COVID-19 in Italy, particularly in the province of Bergamo (the most severely affected), as an example of how, in the face of an unprecedented tragedy, taking action (albeit belatedly) – including imposing a very strict lockdown – can largely resolve the situation within approximately two months. The measures taken here ensured that Bergamo hospital, which was confronted with rapidly rising numbers of very ill COVID-19 patients requiring hospitalisation, was able to meet the initial challenges of the pandemic. We also highlight the importance of coordinating the easing of containment measures to avoid what can currently be observed in other countries especially in Latin American and India, where this approach has not be adopted, and a dramatic resurgence of COVID-19 cases and an increase in the number of hospitalisations and deaths have been reported.